2020
DOI: 10.33206/mjss.581860
|View full text |Cite
|
Sign up to set email alerts
|

External Debt and Economic Growth in Transition Countries: Case of Kyrgyzstan

Abstract: In many developing countries, out of shortage of savings and capital external resources as external debt, foreign direct investment and transfers play significant role in the fostering economic growth and development. The aim of this paper is to investigate the impacts of external public debt, current transfers and foreign direct investments on GDP of Kyrgyz Republic. By using quarterly data during 2000Q1-2017Q3 and the ARDL estimation method, the long-rum cointegration relationship between current transfers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The study of the Kyrgyz Republic's external debt was also conducted by J. Ganiev et al (2020), point to its significant recent growth. The researchers concluded that the country is dependent on foreign revenues, which led them to recommend that main recommendations were given as to how the Kyrgyz Republic can improve its current situation in terms of debt reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the Kyrgyz Republic's external debt was also conducted by J. Ganiev et al (2020), point to its significant recent growth. The researchers concluded that the country is dependent on foreign revenues, which led them to recommend that main recommendations were given as to how the Kyrgyz Republic can improve its current situation in terms of debt reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the Kyrgyz Republic's external debt was also conducted by J. Ganiev et al (2020), point to its significant recent growth. The researchers concluded that the country is dependent on foreign revenues, which led them to recommend that main recommendations were given as to how the Kyrgyz Republic can improve its current situation in terms of debt reduction.…”
Section: Introductionmentioning
confidence: 99%